Pattern-Oriented Software Architecture For Dummies. - Hanmer, Robert (Wiley, 2012)
Implement programming best practices from the ground up Imagine how much easier it would be to solve a programming problem, if you had access to the best practices from all the top experts in the field, and you could follow the best design patterns that have evolved through the years. Well, now you can. This unique book offers development solutions ranging from high-level architectural patterns, to design patterns that apply to specific problems encountered after the overall structure has been designed, to idioms in specific programming languages--all in one, accessible, gu.